The Personal Selling & Digital Marketing on Purchase Decision of Insurance Policy - Kurnia Kurnia; Rani Rifani (STIE Amkop Makassar, 2020)
This study aims to analyze the effect of personal selling and digital marketing on purchasing decisions for insurance policies at PT. QBE General Insurance Indonesia, Makassar Branch. This research data comes from the results of questionnaires to 87 customers of PT. QBE, Makassar Branch. Regarding the purchase decision of an insurance policy using a multiple regression analysis system, the results of the study indicate that personal selling and digital marketing have a partial effect on purchasing decisions with digital marketing. The results of this study also show that personal selling and digital marketing have a positive effect simultaneously on insurance policy purchasing decisions.